2014
DOI: 10.1590/1678-775720130591
|View full text |Cite
|
Sign up to set email alerts
|

Caries-free subjects have high levels of urease and arginine deiminase activity

Abstract: ObjectivesThis study investigated the relationship between urease and arginine deiminase system (ADS) activities and dental caries through a cross-sectional study.Material and MethodsUrease and ADS activities were measured in saliva and plaque samples from 10 caries-free subjects and 13 caries-active. Urease activity was obtained from the ammonia produced by incubation of plaque and saliva samples in urea. ADS activity was obtained from the ammonia generated by the arginine-HCl and Tris-maleate buffer. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 29 publications
4
40
1
1
Order By: Relevance
“…Urease activity was 177% higher than the enzyme activity present in the high caries rate group, while ADS activity was 22% higher in the zero caries group, but without any statistical differences. Compared with Reyes et al study, 23 the differences observed in the present study was lower, both study were made with the same methodology, were ADS activity in saliva was 448% higher in caries free patients, it could be explained because oral imbalances in children incipient stages, not produce caries cavitated lesions yet, compared with adult over 18 years old, that had no previous history of caries.…”
Section: Discussioncontrasting
confidence: 68%
“…Urease activity was 177% higher than the enzyme activity present in the high caries rate group, while ADS activity was 22% higher in the zero caries group, but without any statistical differences. Compared with Reyes et al study, 23 the differences observed in the present study was lower, both study were made with the same methodology, were ADS activity in saliva was 448% higher in caries free patients, it could be explained because oral imbalances in children incipient stages, not produce caries cavitated lesions yet, compared with adult over 18 years old, that had no previous history of caries.…”
Section: Discussioncontrasting
confidence: 68%
“…For these reasons, antimicrobial properties of probiotics may not be sufficient for effectively preventing dental caries (ten Cate and Zaura, 2012) and the ability to restore the microbial ecological balance after pH acidification, for instance by alkali production, is a promising probiotic feature (Huang et al, 2015). Production of ammonia from urea or arginine by several oral bacteria has been shown to efficiently buffer salivary pH and has been associated to a reduction in caries risk (Reyes et al, 2014; Moncada et al, 2015). The analysis of the genome of Streptococcus dentisani revealed all genes from the arginolytic pathway, including the arginine deiminase and the carbamate kinase, a feature which appears to be common to all members of the cluster (Jensen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some clinical studies have shown interplay between biofilm ammonia production and dental caries status, suggesting that alkali generation plays an important role in the subject's caries experience [Nascimento et al, 2009;Reyes et al, 2014], the buffering effect of arginine-mediated ammonia production is limited [Wolff et al, 2013]. It has been shown that the arginine-deiminase system is already activated even after 4 weeks of arginine use [Nascimento et al, 2014].…”
Section: Discussionmentioning
confidence: 99%